Core References in Introductory Social Psychology and Developmental Psychology Textbooks. (March 2017) - Whitehead, George I.; Smith, Stephanie H.; Losonczy-Marshall, Marta
The purpose of the present study was to identify the core references in introductory textbooks in two sub-disciplines of psychology: social psychology and developmental psychology. One research question was the extent to which the common references in these textbooks present the trends in contemporary research in each sub-discipline. An analysis of the reference sections of 10 introductory social psychology textbooks and 15 developmental psychology textbooks found a small set of common references for each subject area. The results yielded three additional effects. First, there were more common references across social psychology textbooks than across developmental psychology textbooks. Second, authors of social psychology textbooks used journal articles as common references more often than books, whereas authors of developmental psychology textbooks used books as common references more than journal articles. Third, the majority of the core references were published prior to 2000. Implications of these findings for teachers of psychology were discussed.